Prevention of Mother-to-Child HIV Transmission Service Utilization among Pregnant Women in Northeast Ethiopia: A Cross-Sectional Survey - Betregiorgis Zegeye; Gorems Lemma; Abebe Balcha; Mitku Mammo Taderegew (Scientifica)
Background. Targeting pregnant women attending antenatal care clinics provides a unique opportunity for implementing the Prevention of Mother-to-Child Transmission (PMTCT) programs against human immunodeficiency virus (HIV) infection of newborn babies. The objective of this study was to assess the PMTCT service utilization rate and to characterize its reasons among pregnant women attending antenatal care clinics at selected public health facilities in Debre Berhan Town, Northern Ethiopia. Methods. A facility-based cross-sectional survey was conducted among 355 pregnant women from May 1 to June 15, 2019. The participants were selected by systematic random sampling technique, and data were collected using a pretested interviewer-administered structured questionnaire. Descriptive statistics like frequency, mean, and standard deviation were reported using text, table, and graphs. Results. The mean ages of the respondents were 24 (±5.6) years, and the majority of the respondents (287 (80.8%)) were urban residents. In this study, prevention of mother-to-child HIV transmission service utilization rate was 86.8%. The most frequently mentioned reasons for not utilization of services were fear of stigma and discrimination (42.6%), fear of rejection by partner (19.1%), fear of positive test results (17.0%), lack of awareness (12.7%), and wastage of time (8.5%). Hence, continuous health education and comprehensive counseling are necessary to increase the awareness and reduce stigma, fear of the positive result, and partner rejection.